Assessing genetic diversity of tiger shrimp Penaeus monodon Fabricius, 1798 utilising microsatellite DNA markers - P. V. Mini; Prithvisagar, K. S.; Iddya , Karunasagar; Karunasagar, Indrani (Indian Journal of Fisheries, 2025)
The giant tiger shrimp, Penaeus monodon Fabricius, 1798 is a significant commercial shrimp species, yet limited information is available on the genetic makeup and diversity of its natural populations. As aquaculture industry relies on wild populations for breeding, understanding their genetic makeup is vital for resource management and diversity preservation. While selective breeding typically targets observable traits, incorporating genetic markers for traits like growth and disease resistance can improve breeding programs. In this study, highly variable microsatellite DNA markers, were used to analyse the genetic variation among P. monodon populations in India. The study found these markers to be highly polymorphic, enabling clear population differentiation and revealing significant genetic sub-division, including a marked distinction between east and west coast populations. Such polymorphic microsatellite loci are valuable tools for gene mapping and pedigree analysis in P. monodon. Keywords: Alleles, Genetic variation, Microsatellite markers, Penaeus, Polymorphism